2005
DOI: 10.1353/jhe.2005.0039
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Department and Discipline in Doctoral Student Attrition: Lessons from Four Departments

Abstract: and the anonymous reviewers for candid and substantive feedback, support and encouragement over too many years.At least 40% of the students who begin a doctoral program fail to complete it. This remarkable fact is one of the hidden flaws of a system usually touted as the crown jewel of the American higher education system. American graduate education is generally regarded as the best in the world, and yet, at the turn of the century, many researchers, administrators, government agencies, foundations, professio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
421
0
14

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 519 publications
(454 citation statements)
references
References 49 publications
19
421
0
14
Order By: Relevance
“…In the high-quality doctoral process the starting points of the individual doctoral students are recognized, the process is carefully planned and attention is paid to high objectives set for the doctoral education (Golde, 2005). The doctoral students already have expertise and networks which can be strengthened in the doctoral education, even though the naturally accumulated capital and its individual dimensions cannot be absolutely presented (Bansel, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the high-quality doctoral process the starting points of the individual doctoral students are recognized, the process is carefully planned and attention is paid to high objectives set for the doctoral education (Golde, 2005). The doctoral students already have expertise and networks which can be strengthened in the doctoral education, even though the naturally accumulated capital and its individual dimensions cannot be absolutely presented (Bansel, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The doctoral degree is not only an educational title or a personal achievement but versatile knowledge and skills to be utilized (Golde, 2005). The majority of the future doctors move to or continue in the employment of other areas of working life and only a fraction of them will continue their career in academic assignments (Boud & Lee, 2009;Baker & Lattuca, 2010).…”
Section: Doctoral Student In the Changing Contextsmentioning
confidence: 99%
“…Lee (2009) indicated that some of the challenges faced by nursing students enrolled in doctoral studies were due to financial issues, problems with the supervisors and lack of academic self-discipline. In their study Golde (2005) indicated that some of the major challenges which students faced that ultimately lead to the student dropout included isolation of the student from the department and mismatch of student's own expectation and programmatic goals. Nerad and Miller (1996), found that lack of care shown by faculty advisor and lack of adequate financial support were the major challenges faced by the students in completion of their doctoral degrees.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies have shown the that majority of doctoral students are capable of completing their degrees and many of the barriers that students face pertain to institutional and program characteristics (Bowen & Rudenstine, 1992;Golde, 2005;Lovitts, 2001;Smallwood, 2004).…”
Section: Summary Of the Program Assessmentmentioning
confidence: 99%